Parental autonomy support and future-oriented coping among high school students: Serial mediation of future time perspective and meaning in life - Zeng, Lianping; Peng, Xia; Zeng, Xiaoye; Wang, Hui; Xiao, Shifei; Chen, Yan (Frontiers in Psychology, 2022)
Guided by the ecosystem theory, we explored the effects of parental autonomy support on future-oriented coping and its influencing mechanisms among high school students. A total of 726 high school students from a high school in Guizhou Province of China completed questionnaires effectively. The results showed a positive correlation between parental autonomy support, future time perspective, meaning in life, and future-oriented coping. Parental autonomy support affected future-oriented coping directly and through three indirect paths: the mediating role of future time perspective, the mediating role of meaning in life, and the serial mediating role of both future time perspective and meaning in life. The results suggested that parental autonomy support can promote future-oriented coping of high school students through the effects of future time perspective and meaning in life. This study deepens the understanding of the mechanism of the relationship between parental autonomy support and future-oriented coping in high school students, which has important implications for promoting future-oriented coping in high school students.